Clinical Study on Treatment of the Carpal Tunnel Syndrome with CF Herbal Acupuncture - Choi Seok-woo; Shin Min-seop; Park Min-ho; Lim Sung-taek; Shin Jin-cheol; Lee Bu-young; Lee Si-seop; Yook Tae-han (Korean Pharmacopuncture Institute, 2005)
Objective : The purpose of the study was to evaluate if CF herbal acupuncture is more effective than simple acupuncture in the carpal tunnel syndrome. Methods : We classified two groups: CF group(patients treated by CF herbal acupuncture and then treated by acupuncture) and N-CF group(patients treated entirely by acupuncture without other treatment). We evaluated subjective symptoms and Phalen's test of patients after executing, and then analyzed those. Results : 1. Both CF group and N-CF group were statistically significant(p<0.05) in improvement of symptoms and Phalen's test since third times of treatment. 2. It appears that CF group was more effective than N-CF group for treatment of carpal tunnel syndrome. That was statistically significant(p<0.05) since third times of treatment